Republic of Belarus : Financial Sector Assessment Program; Detailed Assessment of Compliance; Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report, 2006)
This Detailed Assessment of Compliance-Basel Core Principles for Effective Banking Supervision on the Republic of Belarus reviews principle-by-principle assessment and authorities' response to the assessment. The legal framework for the regulation and supervision of the financial sector has undergone significant reform. The National Bank of the Republic of Belarus (NBRB) fulfills its responsibilities of authorization, supervision, and regulation of banking institution operations through the Banking Supervision Directorate. The NBRB noted that the authorities continue working on the implementation of international standards of banking supervision.